Elucidating biogeochemical characterization of nitrogen in the vadose zone integrating geochemistry, microorganism, and numerical simulation - Duan, Lei; Liu, Xiaobang; Sun, Yaqiao; Wu, Yakun (The Science of the total environment, 2024)
A thorough comprehension of nitrogen biogeochemical processes in the vadose zone is crucial for the effective prevention and remediation of soil-groundwater system contamination. Despite the growing research on this subject, the full scope of nitrogen biogeochemical characterization in different geological environments remains poorly understood. This study addresses this knowledge gap by integrating geochemical, microbiological and numerical simulation approaches to gain a deeper insight into nitrogen biogeochemistry in agriculture. Our findings indicate the biogeochemical behavior of nitrogen in the vadose zone is mediated by microorganisms, driven by hydraulics, influenced by geological conditions and environmental factors. Along the groundwater flow, NH4+-N was found to be heavily accumulated in the topsoil of 0–40 cm, while NO3−-N was transported and driven by hydrodynamics from both vertical and horizontal directions. Microbial diversity, species composition and functional microorganisms were significantly influenced by soil depth, rather than geomorphological types. Oxidation-reduction potential (ORP), total organic carbon (TOC), soil moisture (MOI), bicarbonate (HCO3−), and ferrous (Fe2+) were identified as the principal environmental factors that regulate nitrogen metabolism and the dominant biochemical processes, encompassing nitrogen fixation, nitrification, and denitrification. Driven by hydrodynamics, NH4+-N, NO2−-N and NO3−-N tend to form distinct biochemical reaction zones in the vertical vadose zone. These areas are dynamic and subject to geomorphologies. It should be noted that NO3−-N can migrate towards groundwater from the clayey sand in the Alluvial Plain, which presents a potential risk of groundwater contamination. The fissure structure of loess may serve as the major transport pathway for groundwater nitrogen contamination in the Loess Tableland. This finding highlights the importance of integrating microbiology, geochemistry and hydraulics to elucidate the biogeochemical processes of nitrogen in the vadose zone with a dynamic mindset. [Display omitted] •The biogeochemical processes of nitrogen in the vadose zone were mainly mediated by microorganisms, driven by hydrodynamic forces, and influenced by the geological physicochemical properties of the surrounding environment.•The biogeochemical regions of NH4+-N, NO2−-N and NO3−-N in the vertical vadose zone were hydraulically driven and dynamic, exhibiting distinct differences between geomorphologies.•ORP, TOC, MOI, HCO3− and Fe2+ were identified as the main environmental drivers for nitrogen biochemical processes.•The high permeability of clayey sand and the fracture structure of loess may result in groundwater nitrate contamination in the Alluvial Plain and Loess Tableland.